Aptitudes de los estudiantes en el aprendizaje de lengua y literatura de décimo año, de educación básica, sección vespertina , del Colegio Nacional en Ciencias Juan Montalvo, del cantón Machala, provincia de El Oro periodo 2012-2013. - Laaz Vaca, Patricia Blanca (2013)
This research is aimed at determining the importance and influence of the skills of students in learning language and literature, identifying a variety of skills cognitive nature, linked to education, taking into account that their implementation is vital to learning significantly analysis promotes reflection and creativity of the student.